Detection of Aspergillus DNA by a nested PCR assay is superior to blood culture in an experimental murine model of invasive aspergillosis - Hummel, Margit; Baust, Corinna; Kretschmar, Marianne; Nichterlein, Thomas; Schleiermacher, Dietlind; Spiess, Birgit; Skladny, Heyko; Mörz, Handan; Hehlmann, Rüdiger; Buchheidt, Dieter (The journal of medical microbiology, 2004)
For diagnosing invasive aspergillosis (IA), an increasing clinical problem in immunocompromised patients, molecular tools are gaining in importance. Detection of Aspergillus DNA in blood samples was investigated by a nested PCR assay in a murine model of experimentally induced IA. Ex vivo, the detection threshold of the PCR assay was determined in blood and organ homogenates of mice. After intravenous injection of Aspergillus fumigatus conidia on different days, growth of colonies was determined in cultures of blood and organs from immunocompetent and immunosuppressed mice and Aspergillus DNA was detected from blood samples by a nested PCR assay. The detection threshold of the PCR assay was as low as 1 c.f.u. ml−1. The assay proved to be more sensitive than cultures of blood, with sensitivity rates between 17.6 and 87.5 % depending on the fungal burden. In conclusion, the nested PCR assay is superior to cultural methods in detecting Aspergillus spp. in murine blood samples.,
Gesehen am 13.05.2022